2019
DOI: 10.3390/sports7050123
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Weight-Cutting in Combat Sports

Abstract: In combat sports, athletes are divided into categories based on gender and body mass. Athletes attempt to compete against a lighter opponent by losing body mass prior to being weighed (i.e., ‘weight-cutting’). The purpose of this narrative review was to explore the current body of literature on weight-cutting and outline gaps for further research. Methods of weight-loss include energy intake restriction, total body fluid reduction and pseudo extreme/abusive medical practice (e.g., diuretics). The influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
95
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(113 citation statements)
references
References 76 publications
6
95
0
2
Order By: Relevance
“…Additionally, excessive fluid consumption can pose a risk to health [ 1 ]. Hydration status may also influence exercise performance, with a large body of research observing hypohydration to negatively influence exercise performance, in some cases following rehydration [ 5 – 7 ], though this research area has been a topic of debate [ 8 , 9 ]. Hypohydration impairs exercise through a range of mechanisms, including a reduction in blood plasma/volume, impaired cardiovascular function, muscle blood flow and thermoregulatory capacity [ 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, excessive fluid consumption can pose a risk to health [ 1 ]. Hydration status may also influence exercise performance, with a large body of research observing hypohydration to negatively influence exercise performance, in some cases following rehydration [ 5 – 7 ], though this research area has been a topic of debate [ 8 , 9 ]. Hypohydration impairs exercise through a range of mechanisms, including a reduction in blood plasma/volume, impaired cardiovascular function, muscle blood flow and thermoregulatory capacity [ 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in total body water (TBW) will not always apply equally to every compartment of fluid throughout the body [ 2 ]. This is especially the case for shifts in body position [ 17 ], during exercise [ 5 ], or during dehydration and rehydration [ 7 ]. For example, exercise causes fluid shifts between different compartments, thus complicating subsequent assessments [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Namely, it has been reported that nearly 90% of judokas engage in RWL on multiple occasions per year [3]. In other combat sports, including mixed martial arts [4][5][6], jujitsu [5,7], Brazilian jiu jitsu [5], boxing [8], taekwondo [5,7,8], kickboxing [5], and wrestling [5,8], 60-80% of athletes have reported to engage in some form of weightcutting. As in other combat sports, judokas often employ radical approaches to induce RWL, applying methods such as reduced fluid intake, caloric deficiency, increased physical activity, plastic suit training, heated room training, and sauna [3,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This form of bio-banding classification could facilitate fair competition and reduce potential injuries [18,19]. However, doubts may be raised about the suitability of body mass-based classification to guarantee fair play in combat sports due to evidence of maturation effect within weight categories in young combat sports [20], although there is an important gap in studies on this subject, and to the widespread adoption of rapid weight loss (RWL) as a common competitive strategy [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…RWL refers to the strategy adopted by most combat sports athletes to temporally reduce their body mass, typically about 2-10%, but with reports of reductions greater than 12% [23,24], a few days before competitions to fit in a lower weight category, in an attempt to gain an advantage against lighter, smaller, and weaker opponents [22]. Achieved only through the combination of aggressive dehydration and starvation methods [24][25][26][27][28], it is a well-established common practice among combat sports athletes [29] whose harmful effects are already known and well documented in the literature [26,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%